Shadow of a bull - Wojciechowska, Maia, 1927-2002. ([Mahwah, N.J.] : Troll Associates, 1987)
Manolo Olivar has to make a decision: to follow in his famous father's shadow and become a bullfighter, or to follow his heart and become a doctor.
"Aladdin books"--Cover.
Keywords: Bullfights -- Fiction; Newbery Medal; Spain -- Fiction